The Correlation of Al-Qur'an Memorization and Arabic Learning Achievement - Erlina, Erlina; Kurniawan, Abdul Haris; Hijriyah, Umi; Ismail, Muhammad Zaky (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2022)
Memorizing Al-Qur'an is an attempt to stick in the memory and heart of the verses that have been memorized. So that, in an effort to memorize requires high concentration can survive well. The goal of this study was to ascertain the connection between learning Arabic and successfully memorizing Al-Qur’an in class X SMA IT Fitrah Insani Kemiling. Correlation quantitative approach was used as research design. The populations in this study were 53 tenth grade students in SMA IT Fitrah Insani Kemiling. Furthermore, the data were analyzed using the product moment correlation from person by first conducting prerequisite tests, namely normality and homogeneity tests. The findings revealed a favorable association, with the calculation of the correlation coefficient (rcount) obtained a score of 0.655, then the score compared with at a significant level of 5% for N = 53 and df = N – 2 = 53 – 2 = 51, the number 0.273 was obtained and it could be seen that was higher than or 0.655 > 0.273, so the null hypothesis (Ho) was rejected and the hypothesis alternative (Ha) was accepted. The level of correlation or relationship included in the "strong" category by looking at = 0.655 and the effective contribution is 42.9%. From the results, it could be seen that memorizing Al-Qur’an had a positive relationship to learning achievement.